Novel therapeutic applications of cardiac glycosides - Prassas, I.; Diamandis, E.P.
Cardiac glycosides are a diverse family of naturally derived compounds that bind to and inhibit Na+/K+-ATPase. Members of this family have been in clinical use for many years for the treatment of heart failure and atrial arrhythmia, and the mechanism of their positive inotropic effect is well characterized. Exciting recent findings have suggested additional signalling modes of action of Na+/K+-ATPase, implicating cardiac glycosides in the regulation of several important cellular processes and highlighting potential new therapeutic roles for these compounds in various diseases. Perhaps most notably, the increased susceptibility of cancer cells to these compounds supports their potential use as cancer therapies, and the first generation of glycoside-based anticancer drugs are currently in clinical trials.
Keywords: 7 ETHYL 10 HYDROXYCAMPTOTHECIN; ANGIOTENSIN RECEPTOR ANTAGONIST; ANTINEOPLASTIC AGENTAN; VIRZELBETA ADRENERGIC RECEPTOR BLOCKING AGENT; BUFADIENOLIDE DERIVATIVEBUFALIN; CARBOPLATIN; CARDENOLIDE DERIVATIVE; CARDIAC GLYCOSIDE; CINOBUFAGIN; CISPLATIN; DIGITALIS; DIGITALIS EXTRACT; DIGITONIN; DIGITOXIGENIN; DIGITOXIN; DIGITOXIN; DIGOXINDIPEPTIDYL CARBOXYPEPTIDASE INHIBITOR; GITOXIN; LANATOSIDE C; MARINOBUFAGENIN; NERIUM OLEANDER EXTRACT; OLEANDRIN; OUABAIN; OXALIPLATIN; PACLITAXEL; PROSCILLARIDIN; UNBS 1450; UNCLASSIFIED DRUG; UNINDEXED DRUG